Ramification of Celiac artery in the pine marten (Martes martes) - Mohammad Hasan Yousefi (The Iranian Journal of Veterinary Science and Technology, 2016)
The pine marten (Martes martes) is a medium sized carnivore rarely found in Iran. The aim of this study was to describe species-specific characteristics of the celiac artery in pine marten. In pine marten examined in this study, it was observed that the celiac artery originated from the ventral aspect of abdominal aorta. The celiac artery was divided into two branches. A thick branch was the common trunk of the splenic and the left gastric arteries, namely the gastrosplenic trunk and the other branch which was thin and longer, namely the hepatic artery. The splenic artery was divided into three branches that supplied the spleen. In the examined pine marten, there were two left gastroepiploic arteries, one originated from the splenic, and the other from the left gastric artery. The hepatic artery was extended to the portal fissure of liver and had five following branches: pancreatic branch, gastroduodenal, right gastric, left hepatic, and right hepatic arteries. The right gastroepiploic artery was originated from the gastroduodenal artery. This is the first report on ramification of the celiac artery in the pine marten